Answer: 36y
---------------------------------------------------------------------------------------
Hehsjrjsownsirieus disowned me because
Answer:
I think its
2.4, square root of 5, 1/2, -7/4, -2
hope this helps :D
The answer is 0.91 because it is
Answer:
1) ![-4](https://tex.z-dn.net/?f=-4)
2) ![-3](https://tex.z-dn.net/?f=-3)
3) ![1](https://tex.z-dn.net/?f=1)
4) ![-2](https://tex.z-dn.net/?f=-2)
5) ![4](https://tex.z-dn.net/?f=4)
Step-by-step explanation:
According to the information given in the exercise, the value of "x" is:
![x = -2](https://tex.z-dn.net/?f=x%20%3D%20-2)
Then:
1) You must substitute
into the expresion
:
![=(-2)-2](https://tex.z-dn.net/?f=%3D%28-2%29-2)
Now, you must evaluate:
![=-4](https://tex.z-dn.net/?f=%3D-4)
2) You have to substitute the given value of "x" into the second expression:
![x-1=(-2)-1](https://tex.z-dn.net/?f=x-1%3D%28-2%29-1)
Finally, evaluating, you get the following result:
![=-3](https://tex.z-dn.net/?f=%3D-3)
3) According to the Zero exponent Rule, any non-zero number with an exponent of zero is equal to 1.
Then, substituting
into the expression
and then evaluating, you get:
![x^0=(-2)^0=1](https://tex.z-dn.net/?f=x%5E0%3D%28-2%29%5E0%3D1)
4) By definition:
![a^1=a](https://tex.z-dn.net/?f=a%5E1%3Da)
Then, substituting
into
and evaluating, you get:
![x^1=(-2)^1=-2](https://tex.z-dn.net/?f=x%5E1%3D%28-2%29%5E1%3D-2)
5) Since:
![a^2=a*a](https://tex.z-dn.net/?f=a%5E2%3Da%2Aa)
When you substitute the given value of "x" into the last expression and then you evaluate, you get:
![x^2=(-2)^2=(-2)(-2)=4](https://tex.z-dn.net/?f=x%5E2%3D%28-2%29%5E2%3D%28-2%29%28-2%29%3D4)